2018
DOI: 10.1007/s00213-018-4980-y
|View full text |Cite
|
Sign up to set email alerts
|

Mutual activation of glutamatergic mGlu4 and muscarinic M4 receptors reverses schizophrenia-related changes in rodents

Abstract: RationaleMetabotropic glutamate receptors and muscarinic M4 receptors have been proposed as novel targets for various brain disorders, including schizophrenia. Both receptors are coupled to Go/i proteins and are expressed in brain circuits that are important in schizophrenia. Therefore, their mutual activation may be an effective treatment and allow minimizing the doses of ligands required for optimal activity.ObjectivesIn the present studies, subactive doses of mGlu4 and M4 activators (LSP4-2022 and VU152100,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 75 publications
(108 reference statements)
2
30
0
1
Order By: Relevance
“…Schedules of administration are presented graphically in Figure 1. The sub-effective doses of VU152100 for each test (0.25 mg/kg for novel object recognition and 0.5 mg/kg for social interaction) were chosen based on our previous research (see [18]). Different vehicles were used throughout the study: (1) 0.9% NaCl, (2) 10% Tween 80 or (3) 10% Tween 80 containing 2% DMSO.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Schedules of administration are presented graphically in Figure 1. The sub-effective doses of VU152100 for each test (0.25 mg/kg for novel object recognition and 0.5 mg/kg for social interaction) were chosen based on our previous research (see [18]). Different vehicles were used throughout the study: (1) 0.9% NaCl, (2) 10% Tween 80 or (3) 10% Tween 80 containing 2% DMSO.…”
Section: Resultsmentioning
confidence: 99%
“…Acute administration of MK-801 is a well-established model of schizophrenia, with high predictive validity for investigating the antipsychotic-like activity of compounds. This model is widely used in a variety of studies, including those performed in our laboratory (for example, [7,18]). Using this model, we showed antipsychotic-like activity of VU152100 in social interaction and in novel object recognition tests [18,30].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, other studies have shown that activation of mGluR4 with the mGluR4 agonist (2S)-2-amino-4-({[4-(carboxymethoxy)phenyl](hydroxy)methyl}(hydroxy)phosphoryl)butanoic acid (LSP4-2022) and the PAMs of mGluR4 (1S,2R)-N1-(3,4-dichlorophenyl)cyclohexane-1,2-dicarboxamide (Lu AF21934) and (E)-4-(2-Phenylethenyl)-2-pyrimidinamine (Lu AF32615) reduced the social interaction deficits induced by the NMDA receptor antagonist MK-801 in rats [102,103,104]. Interestingly, the social interaction deficits induced by MK-801 were not only prevented by pretreatment with LSP4-2022 in mice, but also by a concomitant administration of sub-effective doses of LSP4-2022 and 3-Amino- N -(4-methoxybenzyl)-4,6-dimethylthieno[2,3- b ]pyridine carboxamide (VU152100), a PAM of muscarinic M4 receptor, suggesting that simultaneous activation of mGluR4 and M4 receptors might be beneficial in preventing social interaction deficits elicited by an impaired NMDA receptor function [105].…”
Section: Role Of Mglurs In Social Interactionmentioning
confidence: 99%